Analogs of penfluridol as chemotherapeutic agents with reduced central nervous system activity. Issue 23 (15th December 2018) - Ashraf-Uz-Zaman, Md; Sajib, Md Sanaullah; Cucullo, Luca; Mikelis, Constantinos M.; German, Nadezhda A.
Graphical abstract: Highlights: Anticancer doses of penfluridol inhibit a majority of G-protein coupled receptors. Analysis of antipsychotic pharmacophore allowed to design less toxic analogs. Confirmed in vitro cytotoxicity of analogs, in vivo permeability of the BBB. Clinical chemistry analysis confirmed optimized toxicity profile. Abstract: Several recent reports have highlighted the feasibility of the use of penfluridol, a well-known antipsychotic agent, as a chemotherapeutic agent. In vivo experiments have confirmed the cytotoxic activity of penfluridol in triple-negative breast cancer model, lung cancer model, and further studies have been proposed to assess its anticancer activity and viability for the treatment of glioblastomas. However, penfluridol anticancer activity was observed at a dosage significantly higher than that administered in antipsychotic therapy, thus raising the concern for the potential onset of CNS side effects in patients undergoing intensive pharmacological treatment. In this study, we evaluate the potential CNS toxicity of penfluridol side by side with a set of analogs.